Hydrogen sulfide as a therapeutic agent for diabetic wounds: effects on inflammation and fibroblast pyroptosis - Zhao, Fusheng; Li, Yuanyuan; Hu, Qunying; Xu, Jiali; Zhang, Na; Chen, Yonglan; Jiang, Xinyue; Gu, Chunfu; Zhang, Kexin; Wu, Geng (Frontiers in Immunology, 2025)
IntroductionChronic nonhealing wounds are one of the most serious complications of diabetes mellitus (DM), with limited treatment options. Hydrogen sulfide (H2S) plays a protective role against multiple inflammatory diseases. This study aimed to explore the effects of H2S on diabetic skin wound healing and its underlying mechanisms.MethodsA streptozotocin-induced diabetic rat model was established, and the rats were randomly divided into control, DM, and DM + NaHS (a donor of H2S) groups. Full-thickness wounds were made on the dorsal skin of the rats. H2S levels and H2S-synthesizing enzyme expression were evaluated in the wound tissue. Wound healing, histological changes, inflammasome activation, fibroblast pyroptosis, and phosphorylation of signaling components of nuclear factor kappa B (NF-κB) pathway were assessed.ResultsThe results showed that NaHS administration effectively restored H2S levels and promoted skin wound healing, as evidenced by the amelioration of histological changes and increased collagen deposition in diabetic rats. Meanwhile, NaHS treatment inhibited macrophage M1 polarization and decreased the levels of pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) in diabetic wound tissues, notably, suppressing NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome activation and fibroblast pyroptosis. In addition, NaHS treatment was able to inhibit the activation of NF-κB pathway in the wound tissues.ConclusionTaken together, these results show that H2S promotes skin wound healing in diabetic rats and may be involved in the restoration of H2S levels, inhibition of NLRP3 inflammasome activation, and fibroblast pyroptosis, suggesting that it may be a promising therapeutic agent for treating diabetic skin wounds.